RETENÇÃO E EFEITO PREVENTIVO DE CÁRIE (ICDAS 3-4) UTILIZANDO MATERIAL BIOATIVO: Ensaio Clínico de Boca-Dividida 18 Meses - MESQUITA, Juliana Aguiar Costa (2022)
The association of resin-modified glass ionomer cement with 45S5 has shown significant potential in stopping microcavitated caries lesions, but the clinical application of this experimental material still deserves investigation. Purpose: To evaluate the retention and clinical quality of resin-modified glass ionomer cement (RMGIC) associated with 45S5 bioglass (RMGIC/45S5) and its influence on the progression of ICDAS 3 and 4 caries lesions in permanent molars after 18 months. Materials and Methods: Fifty-two molars with moderate caries lesions (ICDAS 3 and 4) were selected. After randomization of the side, the molars were treated, without preparation, with IVMRGI (control) or IVMRGI/45S5 (experimental), completing the randomized clinical trial of split-mouth. Volunteer characteristics were examined at baseline and after 18 months to assess the number of carious lesions (DMFT), gingival health status [Visible Plaque Index (IPV) and Gingival Bleeding Index (GBI)]. In addition, salivary flow rate and buffering capacity were analyzed. Treated teeth were analyzed for sealant retention, severity (ICDAS) and activity (NYVAD) of caries lesions after 18 months of cavity sealing. Wilcoxon and Fisher Exact tests were used for data evaluation. Results: The mean salivary flow and buffering capacity of the patients were respectively 1.1774g/min and 1.4826 Meq/pH/ml. After 18 months, there was a significant increase in DMFT and ISG of patients compared to baseline (p< 0.05), and IPV did not differ between different periods. Both MRGIC and MRGIC/45S5 materials showed high rates of total loss (> 70%) with no statistically significant difference in terms of retention level and material quality after 18 months. Clinical as well as radiographic evaluation did not reveal statistical difference between the materials when considering the levels of stoppage and caries progression (p > 0.05). Conclusion: The addition of 45S5 to IVGIC did not change the retention, quality of the restorations and the stoppage of carious lesions after 18 months of follow-up.